Molten salt carbon felt oxidation for VRFB electrode performance improvement - Piwek Justyna; Gonzalez Gabriel; Peljo Pekka; Frackowiak Elzbieta (Elsevier Ltd, 2025)
In this study, carbon felt (CF) electrodes were chemically treated using alkali metal salt (potassium nitrate) in the molten state as a mild oxidizing agent. Various temperatures in the range of 380–500 °C and oxidation duration (up to 12 h) were analyzed in order to find the most appropriate oxidation conditions. As-prepared carbon felts were electrochemically investigated in a three-electrode set-up as well as in a lab-scale vanadium redox flow battery (VRFB). The battery set-up included additional in-situ potential measurements allowing to measure the polarization of each electrode separately and compare the performance of heat- and chemically-treated electrodes. The physico-chemical properties of CFs have been analyzed using X-ray photoelectron spectroscopy (XPS) and other advanced techniques. Combination of extended oxidation time with temperature increase causes satisfactory surface functionalization and enhanced vanadium redox reaction reversibility. The chemically treated samples showed a better performance with lower overpotentials and higher efficiencies. Improved reversibility of V2+/V3+ reaction is obtained for the carbon felt treated with salt presence. What is more, a 4 times reduced CF electrode oxidation time as usually presented in literature (12 h for heat-treated electrodes vs. 3 h for salt- and heat-treated ones) can be achieved with nitrate salt oxidation.